El Excentrico, 1962-02-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 05, 1962 [5 de febrero de 1962]. Ano 12, No 8. Cover has a photograph of the organizing committee of United Food Drive. People could attend on February 25 at the Liberty Theatre if they bring food donations.